Preferences on green home attributes among Malaysian households - Md Jusoh, Zuroni (Scitech Research Organisation, 2015)
Green home concept is an effort made to reduce the impacts of pollution, saving energy and educate Malaysian people with sustainable lifestyle. The aim of this study was to examine consumers preference on green home attributes in Peninsular Malaysia defined by carbon dioxide (CO2) emission, rainwater harvesting system, natural air ventilation, and greeneries area. Self-administered questionnaires were used to obtain necessary data from 300 selected households through stratified random sampling in Kajang and Bandar Baru Bangi, Selangor, located in central west of Penisular Malaysia using questionnaires through face to face. The choice model technique was applied to estimate the non market values for this study. The results show that all the attributes are tested significant in generic form, while only three are tested significant in label form. Two attributes are tested insignificant which is rainwater harvesting system and greeneries area in label form. The estimated implicit values for green home attributes based on Multinomial Logit regression shows that natural indoor air ventilation is the most important attribute. This is followed by green areas, carbon dioxide (CO2) emission and rainwater harvesting system. The findings also reveal that Malaysian society preferred green home as compared to conventional housing based on the attributes. Finally, the study highlighted several recommendations for households, developers and government to stimulate the green home development in Malaysia. Future work should examine the possibility of other attributes effect to Malaysian consumers.